(untitled) (Realidad Empresarial, 2025)
This study analyzed customers’ perceptions of electronic services provided by financial institutions in Guayaquil, Ecuador, based on the TAM-2 technology acceptance model. Variables such as perceived usefulness, ease of use, intention to use, and attitude toward use were explored, which were fundamental for data collection through a mixed, descriptive, and non-experimental methodological approach. A total of 385 users of electronic banking products were surveyed, and three financial experts were interviewed. The results showed that the perceived usefulness of the services is not significantly influenced by third parties, with most users expressing confidence in the transactions conducted and a positive evaluation of the image and quality of the services. Additionally, demonstrability was associated with improvements in transaction efficiency. Regarding ease of use, users considered the services to be easily adaptable and contributory to the efficiency of financial tasks. In terms of the intention to use, a high willingness was observed among users, although concerns emerged about data privacy and lack of familiarity with the technology. Finally, the attitude toward use highlighted the importance of time, ease, security, and accessibility, along with the impact of the social environment and the perceived added value of these services in the user experience.